2021
DOI: 10.3390/audiolres11020026
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Cartilage Conduction Hearing Aids for Speech Perception in Unilateral Aural Atresia

Abstract: Severe conductive hearing loss due to unilateral aural atresia leads to auditory and developmental disorders, such as difficulty in hearing in challenging situations. Bone conduction devices compensate for the disability but unfortunately have several disadvantages. The aim of this study was to evaluate the benefits of cartilage conduction (CC) hearing aids for speech perception in unilateral aural atresia. Eleven patients with unilateral aural atresia were included. Each participant used a CC hearing aid in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…As a result, an improvement in the SRS was observed when wearing CC-HA. This result was similar to the result of the study reported by Akasaka et al [16], who examined the binaural hearing effect of CC-HA in patients with unilateral aural atresia. However, in our study, the average difference with and without the CC-HA was small (approximately 5%), and when the patients with unilateral conductive hearing loss were divided into the purchase and non-purchase groups, there was no significant difference in the improvement of SRS between the two groups.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, an improvement in the SRS was observed when wearing CC-HA. This result was similar to the result of the study reported by Akasaka et al [16], who examined the binaural hearing effect of CC-HA in patients with unilateral aural atresia. However, in our study, the average difference with and without the CC-HA was small (approximately 5%), and when the patients with unilateral conductive hearing loss were divided into the purchase and non-purchase groups, there was no significant difference in the improvement of SRS between the two groups.…”
Section: Discussionsupporting
confidence: 92%
“…The transducer can be attached to the cartilage part in humans via a special double-sided tape. As previous studies stated [12,[23][24][25][26][27], CCHA can be used for sound transmission even in aural atresia. Most issues with bone conduction (BC) hearing aids are related to the properties of the transducer and the form of conduction.…”
Section: Introductionmentioning
confidence: 79%
“…Cartilage conduction (CC) hearing devices are a new option for atretic ears [11][12][13][14][15]. This device delivers sound to the aural cartilage using a small lightweight transducer.…”
Section: Introductionmentioning
confidence: 99%